Adopting Green Practices on Msme’s Culinary Sector: A Relationship Between Consumer Green Purchase Intentions and Adoption Green Practices - Ghazal Erlangga Avicena; Achmad Fajar Hendarman (Universitas KH. Abdul Chalim Mojokerto, 2026)
Indonesia faces critical environmental challenges, with 38.6 million tons of waste generated in 2024 and only 34% properly managed. The food and beverage sector contributes significantly to both economic growth and environmental burden, while culinary MSMEs dominate the business landscape but operate under severe resource constraints. This study examines how consumer green purchase intentions influence green practice adoption in Indonesian culinary MSMEs using the Theory of Planned Behavior (TPB). Using a cross-sectional survey of 301 Indonesian consumers and PLS-SEM analysis, the results show that environmental attitude, subjective norms, and perceived behavioral control significantly influence green purchase intention. Green purchase intention has an exceptionally strong effect on green practice adoption (β = 0.894), fully mediating all TPB antecedents. The model explains 83.4% of the variance in green purchase intention and 79.9% in green practice adoption. The findings confirm that consumer demand is the most powerful driver of sustainability adoption among culinary MSMEs, highlighting the importance of cultivating demand-side pressure alongside supply-side support.